“Diseño del Plan de Marketing, Mediante la Aplicación de la Metodología el Pimte 2014, para fortalecer la prestación de servicios hoteleros en el Hostal “Shamana Huasi”, ubicado en la Parroquia Lumbaqui, Cantón Gonzalo Pizarro, Provincia de Sucumbíos - Jaramillo Lapo, Erika Joanna (2018)
The present study called "Design of the marketing plan, through the application of the PIMTE 2014 methodology, to strengthen the provision of hotel services in the" Shamana Huasi "hostel, located in the Lumbaqui parish, canton Gonzalo Pizarro, Sucumbíos province. It was developed with the purpose of providing the hostel with a proposal aimed at improving its competitive position. The study began with the diagnosis of the current situation of the Hostal Shamana Huasi located in the Lumbaqui parish, canton Gonzalo Pizarro, province of Sucumbíos, using the deductive, inductive and analytical methods. The collection of information for the internal analysis was made through an interview with the owner manager of the hostel and survey of 387 domestic and foreign tourists; while for the internal analysis, secondary sources such as written press and web pages were used; in addition, 8 sheets were produced summarizing the tourist attractions of the Lumbaqui parish. From the analysis of the internal environment strengths and weaknesses were identified, which are presented in the MEFI and from the evaluation of the external environment, the opportunities and threats presented in the MEFE were extracted, with this information the SWOT matrix was elaborated with 5 strategies. Then the marketing plan proposal was elaborated, for the strengthening of the "Shamana Huasi" Hostel through the PIMTE 2014 methodology, developing 6 operational plans in which it describes: objective, strategy, tactics, policy and budget. Afterwards, the Socialization of the marketing plan with those involved was carried out, for which an invitation was made to the staff working in the hostel for a meeting to make known the strategies established in the proposal, for this purpose slides were designed and each one of the operational plans designed to improve the competitive position of the hostel. From the study carried out it is concluded that there are external factors that can favor the growth of the hostel, however internally it is necessary to eliminate weaknesses that limit their development. Faced with this situation, it is recommended to execute the 6 proposed operational plans, which will contribute to improving the current situation of the hostel. For this purpose, the necessary resources must be allocated for the execution of the proposal, in order to guarantee its execution.